Dielectric parameters of phase and belt paper impregnated insulation of power cables - Bezprozvannych, G. V.; Moskvitin, Y. S.; Kostiukov, I. O.; Grechko, O. M. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Medium voltage power cables with paper impregnated insulation remain an important component of power networks. The reliability and efficiency of such cables have been confirmed by their long service life also at nuclear power plants. Problem. It is not possible to directly determine the dielectric parameters of phase and belt paper insulation of power cables. Effective electrical diagnostic systems are required to assess the technical condition of such types of power cable insulation. The aim of the work is to substantiate the methodology for determining the dielectric properties of phase and belt paper impregnated insulation based on cumulative measurements of the electrical capacitance and the tangent of the dielectric loss angle of power cables of nuclear power plants and power networks. Methodology. The developed methodology is based on the solution of a system of linear algebraic equations of the sixth order for determining the dielectric properties of types of paper impregnated insulation of power three-core cables in a metal sheath. Scientific novelty. The differences in the structure of the probing electric field in phase and belt paper insulation depending on the inspection scheme of three-core power cables with sector cores in a metal sheath have been established. The shares of electric energy in the types of insulation under different probing electric field schemes have been determined, which allows determining the tangent of the dielectric loss angle of phase and belt paper insulation. Practical significance. The results of the practical implementation of the developed methodology for assessing the differences in the properties of phase and belt insulation of power cables of nuclear power plants and power network cables during spatial scanning of electrical insulation by frequency and voltage, respectively, are presented.

Силові кабелі середньої напруги з паперовою просоченою ізоляцією залишаються важливою складовою електроенергетичних мереж. Надійність та ефективність таких кабелів підтверджено тривалим терміном експлуатації також на АЕС. Проблема. Безпосередньо визначити діелектричні параметри фазної та поясної паперової ізоляції силових кабелів не виявляється можливим. Для оцінки технічного стану таких видів ізоляції силових кабелів необхідні ефективні електричні системи діагностики. Метою роботи є обґрунтування методології визначення діелектричних властивостей фазної та поясної паперової просоченої ізоляції на підставі сукупних вимірювань електричної ємності та тангенсу кута діелектричних втрат силових кабелів АЕС та електричних мереж. Методика. Розроблена методика ґрунтується на розв’язанні системи лінійних алгебраїчних рівнянь шостого порядку для визначення діелектричних властивостей видів паперової просоченої ізоляції силових трижильних кабелів у металевій оболонці. Наукова новизна. Встановлено відмінності структури зондувального електричного поля у фазній та поясній паперовій ізоляції в залежності від схеми обстеження трижильних силових кабелів із секторними жилами у металевій оболонці. Визначено частки електричної енергії у видах ізоляції за різних схем зондувального електричного поля, що дозволяє визначити тангенс кута діелектричних втрат фазної та поясної паперової ізоляції. Практична значимість. Представлено результати практичної реалізації розробленої методики для оцінки відмінностей властивостей фазної та поясної ізоляції силових кабелів АЕС та кабелів енергомереж при просторовому скануванні електричної ізоляції за частотою та напругою відповідно.
Діелектричні параметри фазної та поясної паперової просоченої ізоляції силових кабелів
Keywords: power cables; paper impregnated insulation; electric field structure; commutation matrix; angle tangent; dielectric loss; силові кабелі; паперова просочена ізоляція; структура електричного поля; матриця комутації; тангенс кута; діелектричні втрати